Vivências do estágio supervisionado no Ensino Fundamental I em uma escola pública em Bragança - PA: uma perspectiva epistemológica da prática pedagógica. - FERREIRA, Thiago da Silva (2024)
This work is about the experiences in a Supervised Internship in elementary schol early years is an essential moment in teacher training as it provides the experience of reality in the classroom, enabling the connection between theory and practice to be truly realized, promoting educational praxis. It is worth highlighting that the aforementioned Internship took place at Escola Municipal de Ensino Fundamental Prof. Jorge Daniel Souza Ramos in Bragança/PA, from 09/05/2023 to 09/22/2023. The objective of this study is to understand the theorypractice relationship in the classroom, from a Praxis epistemology perspective. In this way, the internship is seen as a central axis in the academic training of the future teacher, as it is through this phase of training that the intern has access to the knowledge essential for the construction of identity and pedagogical knowledge/practices in the classroom. For theoretical support, it was supported by some approaches such as Barreiro and Gebran (2006), Antunes (2017), Nóvoa (1995), Pimenta and Lima (2004), Pimenta (2012), Barreiro and Gebran (2015), Tardif (2002), and others. This research is characterized as descriptive, explanatory, and field. Finally, despite the obstacles that arose during the internship, it can be said that the Supervised Internship in Elementary Education brought unique experiences that reaffirmed my commitment to moving forward in training in education, as well as in a possible area of activity as a Pedagogue, recognizing of course that there is still a long way to go, both in terms of theoretical support that underlies the practice, and in experiencing the different realities found in the most diverse classroom contexts and, even at school, ending with a speech by Rios when he states that: “Competence is revealed in action.” (RIOS, 2001, p.88).